2022
DOI: 10.1017/gmh.2022.17
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of common mental disorders among women in the perinatal period: a critical mixed-methods review and meta-analysis

Abstract: Perinatal depression and anxiety account for a high burden of perinatal morbidity and poor psychosocial functioning. There is a growing interest among mental health professionals, to devise interventions to prevent this condition. This review synthesizes evidence for the effectiveness of psychological and psychosocial interventions aimed at the prevention of perinatal depression and anxiety. We also explore qualitative evidence to understand the acceptability and feasibility of these interventions. Using a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
3
13
1
1
Order By: Relevance
“…La evidencia procedió de una revisión sistemática de las intervenciones psicológicas y psicosociales para la prevención de los problemas de salud mental frecuentes en el período posparto (94). Los datos procedieron de Experiencia de la atención posnatal: La evidencia de certeza baja existente sugiere que las intervenciones para prevenir los problemas de salud mental, con componentes aplicados en cualquier momento, pueden reducir la insatisfacción materna en comparación con ninguna intervención o con la atención habitual (8 ensayos, 4007 mujeres; DME 0,36 inferior, IC del 95%: 0,60 inferior a 0,12 inferior).…”
Section: Resumen De La Evidencia Y Consideracionesunclassified
“…La evidencia procedió de una revisión sistemática de las intervenciones psicológicas y psicosociales para la prevención de los problemas de salud mental frecuentes en el período posparto (94). Los datos procedieron de Experiencia de la atención posnatal: La evidencia de certeza baja existente sugiere que las intervenciones para prevenir los problemas de salud mental, con componentes aplicados en cualquier momento, pueden reducir la insatisfacción materna en comparación con ninguna intervención o con la atención habitual (8 ensayos, 4007 mujeres; DME 0,36 inferior, IC del 95%: 0,60 inferior a 0,12 inferior).…”
Section: Resumen De La Evidencia Y Consideracionesunclassified
“…Our results add to the evidence that ‘task shifting’ is an effective and feasible approach to address treatment gaps25 26 and that CBT-based psychosocial interventions can be delivered by NSPs 15 16. Systematic reviews of qualitative studies from LMICs have indicated high levels of acceptance of CBT-based maternal mental health interventions 2 27. However, for non-specialist-delivered interventions to be successful, effective training and supervision structures are essential 14 28.…”
Section: Discussionmentioning
confidence: 59%
“…Anxiety during pregnancy is highly prevalent and adversely impacts maternal and child health outcomes. Prenatal anxiety disorders and anxiety symptoms disproportionately affect pregnant women in low/middle-income countries (LMICs)1 especially in the South Asian region, including 49% in Pakistan,2 55.7% in India3 and 29% in Bangladesh 4. Prenatal anxiety is associated with impaired coping,5 fear of childbirth,6 postnatal anxiety and depression,7 8 and risk of suicide 9.…”
Section: Introductionmentioning
confidence: 99%
“…For prevention, community-based surveys employing PND screening tools and social risk questionnaires (100, 104) can be utilized to identify women with either high social risk or prodromal depressive symptoms. Those found to be at the highest risk can be offered low-intensity interventions as recommended by the WHO and the US Preventive Services Taskforce (101,105). The same surveys could also be used to screen women who have already developed PND.…”
Section: Risk Factors For Pnd Subtypes With Worse Clinical Prognosismentioning
confidence: 99%